Festschrift in honour of professor Eduardo Ismael Murguia Maranon - Chaves Guimaraes, Jose Augusto [UNESP] (Univ Zaragoza, 2016)
A biographical sketch of Professor Ismael Eduardo Murguia Maranon, a leading Peruvian-Brazilian archivist, information scientist and humanist, is provided. Thereafter, the papers offered in his honor by several American academics are presented. These articles delve into the critical perspective of information science, archives and photography that Professor Murguia cultivated along his fruitful life.
Keywords: Eduardo Ismael; Murguia Maranon; Homenaje; Memory